SAT-555 Cytotoxicity of Epstein-Barr Virus Reactivation-Induced TRAb-IgM to Thyrocytes - Nagata, Keiko (J Endocr Soc, 2019)
Epstein-Barr virus (EBV) is a human herpes virus persisting in B lymphocytes, and is occasionally reactivated. Healthy controls as well as Graves’ disease patients have EBV-infected B cells that have TSH receptor antibodies (TRAbs) as their surface globulin (TRAb(+)EBV(+) cells) (1), and peripheral blood mononuclear cells (PBMCs) containing TRAb(+)EBV(+) cells produce TRAbs in reaction to EBV-reactivation induction (2). We proposed the EBV reactivation-induced immunoglobulin (Ig) production which is distinct pathway from the antibody production through germinal center and bone marrow (3). Since this pathway does not contain a germinal center, the majority of produced antibodies are IgM, but not affinity-maturated IgG. However, an EBV reactivation-induced Ig production system can rescue the autoreactive B cells that could not encounter their specific autoantigens and thus never enter lymphoid tissue, and drive autoreactive B cells to differentiate and produce autoantibodies. We observed that patient serum contains considerable amounts of TRAb-IgM (4) One of the characteristic histologies of Graves’ disease is lymphoid cell infiltration often associated with regenerated colloid follicles, suggesting the destructive event of follicular epithelia. We hypothesized that TRAbs, especially induced by EBV reactivation, have the capacity to injure follicular epithelial cells resulting in spreading of autoantigens. We observed that porcine thyroid follicular cells cultured with serum from Graves’ disease patients were often damaged and dying. The levels of cAMP in the lysate of these damaged cells increased. In order to study whether this cell death process is an poptosis or not, we stained these cells by Hoechst 33258, and then performed DNA fragmentation analyses of extracted DNA. However, we could not detect any chromatin condensation or apoptotic DNA ladders. Follicular cell injury was blocked by inactivated serum and anti-human TSH receptor monoclonal antibody instead of patient’s serum. Therefore, we considered that follicular cell injury could be necrosis through TRAbs and the classical pathway of complement activation. We would like to demonstrate these data with further experiments with TRAb-IgM and purified complement. References: (1) Nagata et al., Autoimmunity 2014; 47: 193-200. (2) Nagata et al., Autoimmunity 2015; 48: 328-335. (3) Nagata et al. Viral Immunology 2017; 30: 240-249. (4) Kumata et al., Viral Immunology 2016; 29: 459-463.